PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASA LAJU REAKSI DI KELAS XI IPA SMAN 5 PEKANBARU - Novizal, Roni; Erna, Maria; Azmi, Johni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve student achievement in the subject reaction rate through the implementation of learning model Think Pair Share (TPS) in class XI IPA SMAN 5 Pekanbaru. Type of research is experimental study using pretest-posttest design. Research conducted at SMAN 5 Pekanbaru. Samples of this research is class XI.IA4 as experimental class and the students in the class as a class XI.IA6 control, this sample was randomly selected after tests of normality and homogeneity in both samples. In the process of classroom learning and classroom control experiment using the scientific approach to the curriculum SBC beracuan. Experimental class is the class that was given treatment by using model Think Pair Share (TPS), while the control class is the class that was treated using the usual method implementation discussion. Based on the results of hypothesis testing data analysis obtained t> t table ie 1.83> 1.67, this shows the differences in learning outcomes of students before and after the study material reaction rate with and without the use of learning model Think Pair Share (TPS) in class XI IPA SMAN 5 Pekanbaru.